2016
DOI: 10.1007/s00234-016-1738-2
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord diffusion tensor imaging in patients with sensory neuronopathy

Abstract: DTI-based analysis enables in vivo detection of posterior column damage in sensory neuronopathy patients and is a useful diagnostic test for this condition. It also helps the differential diagnosis between sensory neuronopathy and distal polyneuropathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
3
4
0
Order By: Relevance
“…This neuroimaging signature reflects damage resulting from dorsal root ganglia (DRG) degeneration. Indeed, these radiological changes are very similar to those reported in other disorders characterized by extensive DRG damage, either inherited (eg, Friedreich's ataxia) or acquired (immune‐mediated sensory neuronopathies) 10,25 …”
Section: Discussionsupporting
confidence: 79%
“…This neuroimaging signature reflects damage resulting from dorsal root ganglia (DRG) degeneration. Indeed, these radiological changes are very similar to those reported in other disorders characterized by extensive DRG damage, either inherited (eg, Friedreich's ataxia) or acquired (immune‐mediated sensory neuronopathies) 10,25 …”
Section: Discussionsupporting
confidence: 79%
“…Whereas Camdessanche reported that 5% of sensory neuronopathy patients had abnormal spinal-cord MRI studies, [ 37 ] most other studies reporting on more than 10 patients have reported that 50% to 85% of sensory neuronopathy patients have abnormal spinal-cord MRI studies. [ 15 18 , 38 40 ] Therefore, our findings reaffirm how the multidisciplinary group of physicians who may encounter sensory neuronopathies can recognize and utilize spinal-cord MRI as a valuable adjunctive marker. Furthermore, our study describes how spinal-cord MRI can be used as a longitudinal indicator of treatment efficacy.…”
Section: Discussionsupporting
confidence: 69%
“…Neuroimaging of the cortical and subcortical regions in patients with painful neuropathies have identified alterations in activity and functional connectivity that correlate with the subjects' neuropathic pain characteristics and treatment, including in patients with low back pain [32], PHN [117], diabetic polyneuropathy [118], neuroma pain [119], phantom limb [120], and CRPS [121,122]. Additionally, structures in the mesencephalic reticular formation (including possibly the PAG and nucleus cuneiformis) that, in preclinical studies, have been shown to be essential to mechanical allodynia after peripheral nerve injury, demonstrate increased neuronal activity on functional neuroimaging in a human capsaicin-evoked secondary hyperalgesia model [123].…”
Section: Evidence For Central Mechanisms: Clinicalmentioning
confidence: 99%